Evaluation of the Inhibitory Activities of COVID‐19 of Melaleuca cajuputi Oil Using Docking Simulation. Issue 21 (2nd June 2020) - My, Tran Thi Ai; Loan, Huynh Thi Phuong; Hai, Nguyen Thi Thanh; Hieu, Le Trung; Hoa, Tran Thai; Thuy, Bui Thi Phuong; Quang, Duong Tuan; Triet, Nguyen Thanh; Anh, Tran Thi Van; Dieu, Nguyen Thi Xuan; Trung, Nguyen Tien; Hue, Nguyen Van; et al.
Abstract: GC‐MS was applied to identify 24 main substances in Melaleuca cajuputi essential oil (TA ) extracted from fresh cajeput leaves through steam distilling. The inhibitory capability of active compounds in the TA from Thua Thien Hue, Vietnam over the Angiotensin‐Converting Enzyme 2 (ACE2) protein in human body ‐ the host receptor for SARS‐CoV‐2 and the main protease (PDB6LU7) of the SARS‐CoV‐2 using docking simulation has been studied herein. The results indicate that the ACE2 and PDB6LU7 proteins were strongly inhibited by 10 out of 24 compounds accounting for 70.9% in the TA . The most powerful anticoronavirus activity is expressed in the order: Terpineol (TA2 ) ≈ Guaiol (TA5 ) ≈ Linalool (TA19 ) > Cineol (TA1 ) > β‐Selinenol (TA3 ) > α‐Eudesmol (TA4 ) > γ‐Eudesmol (TA7 ). Interestingly, the synergistic interactions of these 10 substances of the TA exhibit excellent inhibition into the ACE2 and PDB6LU7 proteins. The docking results orient that the natural Melaleuca cajuputi essential oil is considered as a valuable resource for preventing SARS‐CoV‐2 invasion into human body. Abstract : This is the first time to simulate the inhibitory effect of compounds in Melaleuca cajuputi oil to the main proteins of SARS‐CoV‐2 (PDB6LU7) and its host receptor (ACE2). They are strongly inhibited by the individual inhibition as well as the synergistic interaction of 10 out of 24 compounds accounting for 70.9% in this oil. The results orient that Melaleuca cajuputi oil is considered as a valuable resource for SARS‐CoV‐2 prevention.